2001
DOI: 10.1096/fj.00-0538com
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac phosphodiesterase 5 (cGMP‐specific) modulates β‐adrenergic signaling in vivo and is down‐regulated in heart failure

Abstract: Recent studies implicate increased cGMP synthesis as a postreceptor contributor to reduced cardiac sympathetic responsiveness. Here we provide the first evidence that modulation of this interaction by cGMP-specific phosphodiesterase PDE5A is also diminished in failing hearts, providing a novel mechanism for blunted beta-adrenergic signaling in this disorder. In normal conscious dogs chronically instrumented for left ventricular pressure-dimension analysis, PDE5A inhibition by EMD82639 had modest basal effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
177
3
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(194 citation statements)
references
References 47 publications
13
177
3
1
Order By: Relevance
“…There has been a dominant view that PDE5 is not present in the myocardium (11) recent study where abundant expression of PDE5 was observed in isolated canine ventricular cardiomyocytes with immunohistochemistry (23). In agreement with this observation, our study demonstrated for the first time the presence of PDE5 in murine ventricular cardiomyocytes (Fig.…”
Section: Effect Of Sildenafil On Bcl-2 Expression In Inos-or Enosdefisupporting
confidence: 91%
See 2 more Smart Citations
“…There has been a dominant view that PDE5 is not present in the myocardium (11) recent study where abundant expression of PDE5 was observed in isolated canine ventricular cardiomyocytes with immunohistochemistry (23). In agreement with this observation, our study demonstrated for the first time the presence of PDE5 in murine ventricular cardiomyocytes (Fig.…”
Section: Effect Of Sildenafil On Bcl-2 Expression In Inos-or Enosdefisupporting
confidence: 91%
“…J, bar diagram showing quantitative data from three independent experiments. PDE5 band (90 -100 kDa) were observed, which is consistent with the previously reported PDE5A in dog cardiomyocytes (23). Furthermore, using immunohistochemistry and laser confocal microscopy, the green fluorescence for PDE5A in normal isolated myocyte was clearly evident, thereby confirming the localization of PDE5A in adult mouse cardiomyocytes (Fig.…”
Section: Effect Of Sildenafil On Bcl-2 Expression In Inos-or Enosdefisupporting
confidence: 90%
See 1 more Smart Citation
“…Erectile dysfunction (ED) is a common medical condition linked both to endothelial dysfunction [1][2][3][4][5][6][7][8][9][10][11][12][13] as well as multiple other comorbid conditions. [14][15][16][17] Historically, the treatment for ED has been limited to a selected group of specialists, namely urologists and sexual therapists.…”
Section: Introductionmentioning
confidence: 99%
“…All studies using either RT-PCR or Northern blot have demonstrated PDE5 mRNA expression in the heart, 1-5 and a separate study using immunohistochemical staining and functional assays also demonstrated PDE5 expression in canine cardiomyocytes. 6 However, PDE5 enzymatic activity was reported to be absent in a human ventricular homogenate. 7 Two PDE5 isoforms, PDE5A1 and PDE5A2, have been identified in humans and dogs.…”
Section: Introductionmentioning
confidence: 99%